Household food insecurity associated with stunting and underweight among preschool children in Antioquia, Colombia (2009)
ABSTRACT: Objective. To assess criterion validity of a household food security scale through its associations with child health status in participants of the Colombian Plan for Improving Food and Nutrition in Antioquia (Mejoramiento Alimentario y Nutricional de Antioquia (MANA)). Methods. A 12-item household food security survey (Colombian Household Food Security Scale, CHFSS) was applied to a cross-sectional stratified random sample of 2 784 low-income households with preschool children receiving MANA food supplements in Antioquia, Colombia. Anthropometrics and health status of the children were also assessed. Chi-square tests were used to initially compare child health status and household food security status. Logistic regression models were further developed to assess this relationship in bivariate and multiple regression models. Results. Statistically significant associations were found between household food insecurity and diagnoses of children’s diarrhea, respiratory infections, and parasitosis (P < 0.0001). The risk for child stunting and underweight increased in a dose–response way as food insecurity became more severe. Conclusions. Our research establishes an important link between household food insecurity and child nutritional status in participants of a food assistance program. The results affirm the criterion validity of the CHFSS, establishing the proposed instrument as a valid measure for food insecurity with high-risk populations.